2013
DOI: 10.1097/rlu.0b013e318279fd3d
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Imaging With 18F-Fluoroerythronitroimidazole Integrated PET/CT and Immunohistochemical Studies in Non–Small Cell Lung Cancer

Abstract: T/Me ratio provides a noninvasive parameter for quantization of (18)F-FETNIM uptake on PET/CT. T/Me ratio is correlated with a worse outcome and with the expression of HIF-1α, GLUT-1, and VEGF, all up-regulated under hypoxic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 20 publications
1
45
0
1
Order By: Relevance
“…Grönroos et al [189] Yang et al [60] NA Hu et al [85] Grönroos et al [189] , Tolvanen et al [190] , Yang et al [60] Hu et al [85] , Li et al [84] Lehtiö et al [99] , Lehtiö et al [191] , Lehtiö et al [192] , Vercellino et al [193] , Yue et al [194] […”
Section: F]ef5unclassified
See 1 more Smart Citation
“…Grönroos et al [189] Yang et al [60] NA Hu et al [85] Grönroos et al [189] , Tolvanen et al [190] , Yang et al [60] Hu et al [85] , Li et al [84] Lehtiö et al [99] , Lehtiö et al [191] , Lehtiö et al [192] , Vercellino et al [193] , Yue et al [194] […”
Section: F]ef5unclassified
“…In contrast to these results, other authors did not find a predictive value for [ 18 F]FMISO after chemoradiation [82,83] . In other patients treated with chemoradiation, a threshold of tumor-to-blood ratio > 1.9 for [ 18 F]FETNIM [84,85] and > 3.0 for [Cu]ATSM [86] was associated with poor overall survival and tumor response, respectively. In addition, a number of studies have evaluated the changes in hypoxia tracer uptake during therapy.…”
Section: Determination Of Clinically Relevant Hypoxiamentioning
confidence: 99%
“…A significant but weak correlation between VEGF expression and 18 F-FMISO uptake was observed in newly diagnosed glioma patients, but not in those with recurrent glioma. Hu et al [51] investigated the relationship between [ 18 F]fluoroerythronitroimidazole ( 18 F-FETNIM) uptake and expression of HIF-1 α , VEGF, and glucose transporter 1 (GLUT-1) in nonsmall cell lung cancer. A positive correlation existed between the tumor-to-muscle ratio of 18 F-FETNIM and the expression of each of these HIF-1 α targets.…”
Section: Molecular Imaging Of Hif-1-active Tumor Microenvironmentsmentioning
confidence: 99%
“…Hu et al have tested (18)F-fluoroerythronitroimidazole PET/CT that uses an assessment of tumor hypoxia to evaluate the prognosis on a group of thirty-two NSCLC patiens 154 . A clinical study examining antisense oligodeoxynucleotide binding HIF-1α showed a decrease in HIF-1 protein levels and mRNA levels in some of its target genes in tumor cells 155 .…”
Section: Future Perspectivesmentioning
confidence: 99%